Analysis on the intention and influencing factors of free influenza vaccination among the elderly people aged 70 and above in Hangzhou in 2022 - Che, Xinren; Liu, Yan; Gu, Wenwen; Wang, Fangying; Wang, Jun; Jiang, Wei; Du, Jian; Zhang, Xiaoping; Xu, Yuyang; Zhang, Xuechao; Wang, Jing (Frontiers in Public Health, 2023)
Background Although influenza vaccination is recommended for people aged 70 and above in Hangzhou, and the vaccine is provided free of charge, the elderly influenza vaccination rate is still low. The purpose of this study was to understand the barriers and motivations of older people in deciding to receive free influenza vaccine through questionnaires. Methods The method of stratified random sampling was adopted to take samples. A questionnaire survey was conducted among the elderly aged 70 years and above by face-to-face interview or telephone interview. Results A total of 11,663 elderly people aged 70–100 years were successfully and effectively interviewed. 85.98% of the respondent were willing to get the influenza shot, 8.91% were unwilling to get the influenza shot, and 5.11% were on vaccine hesitancy. The people of age of 70–79 years old (hesitancy: OR70 79 = 0.668, 95%CI: 0.571 0.782, Unwilling: OR70 − 79 = 0.755, 95%CI: 0.622 0.916), primary school degree or below (hesitancy: ORSecondary school degree or above = 1.467, 95%CI: 1.249 1.724, Unwilling: ORSecondary school degree or above = 1.255, 95%CI: 1.028 1.535), remote areas (hesitancy: ORnear central urban area = 2.111, 95%CI: 1.604 2.778, ORcentral urban area = 2.957, 95%CI: 2.255 3.877, Unwilling: ORnear central urban area = 1.687, 95%CI: 1.230 2.313. ORcentralurbanarea = 2.218, 95%CI: 1.626 3.027), and convenient for movement (hesitancy: ORyes = 0.494, 95%CI: 0.420 0.580, Unwilling: ORyes = 0.585, 95%CI: 0.480 0.713), understanding of the free vaccine policy (hesitancy: ORunderstand = 0.204, 95%CI: 0.171 0.245, Unwilling: ORunderstand = 0.164, 95%CI: 0.128 0.210), influenza knowledge level≥ 13 points (hesitancy: OR≥13points = 0.628, 95%CI: 0.533 0.739, Unwilling: OR≥13points = 0.538, 95%CI: 0.437 0.662), influenza vaccine knowledge level≥ 12 points (hesitancy: OR≥12points = 0.422, 95%CI: 0.350 0.508, Unwilling: OR≥12points = 0.370, 95%CI: 0.290 0.472), and social trust level ≥ 12 points (hesitancy: OR≥12points = 0.134, 95%CI: 0.112 0.160, Unwilling: OR≥12points = 0.220, 95%CI: 0.180 0.269) are more willing to receive free influenza vaccine. Conclusion The proportion of elderly people aged 70 and above who are willing to receive free influenza vaccine is high in Hangzhou. But the level of knowledge about influenza, vaccine and trust in society is low. The government should continue to improve the elderly's awareness and trust in society through medical staff, family members, television and radio media, and guide the elderly to actively vaccinate against influenza. Effective publicity should be carried out through the above channels to guide the elderly to actively vaccinate against influenza.